Changing trend of microbiologic profile and antibiotic susceptibility of the microorganisms isolated in the neonatal nosocomial sepsis: a 14 years analysis. (1st November 2020) - Mutlu, Mehmet; Aslan, Yakup; Aktürk Acar, Filiz; Kader, Şebnem; Bayramoğlu, Gülçin; Yılmaz, Gürdal
Abstract: Objective: Neonatal sepsis, especially nosocomial sepsis (NS) is one of the main causes of mortality and morbidity in neonates. Our aim was to investigate microorganisms responsible for NS and antimicrobial susceptibility patterns and to compare them in a different period. Methods: Blood culture registers from the Microbiology Laboratory were reviewed for the study population. The neonates with proven NS were enrolled in the study. Microorganisms responsible for NS and antimicrobial susceptibility patterns were recorded Results: The incidence of Gram-positive, Gram-negative, and fungal microorganisms were 61.6% ( n  = 570), 27.1% ( n  = 251) and 11.3% ( n  = 104), respectively. The most common isolated Gram-positive, Gram-negative pathogens and fungi were Coagulase-negative staphylococci (CoNS), Klebsiella pneumoniae, and C. guilliermondii . There was an increasing resistance rate among common nosocomial pathogens especially oxacillin resistant CoNS strains and increasing rate for extended-spectrum beta-lactamase (ESBL) positive microorganisms. Low susceptibility was detected to commonly used antibiotics for empirical treatment in neonatal sepsis. Conclusions: Our result showed that multiresistant microorganisms, especially oxacillin-resistant staphylococci and gram-negative bacilli resistant to cephalosporin have an increasing rate. Every unit should evaluate the causative agents and antimicrobial susceptibilities in order to select an appropriate regime for nosocomial sepsis. Periodic surveillance of organisms and their antibiotic resistance patterns in every unit might help physicians for proper selection of antibiotics for treatment of neonatal NS.